Continuous carbon fiber reinforced silicon carbide sagger and preparation method thereof

By using continuous carbon fiber reinforced silicon carbide scr, combined with the combination of carbon fiber cloth and silicon carbide matrix and liquid phase densification process in the negative electrode material of lithium battery, the existing scr, the problems of poor performance and short life are solved, and high strength is achieved , wear resistance and low-cost material preparation, suitable for sintering of negative electrode materials for lithium battery.

CN119306497APending Publication Date: 2025-01-14HUNAN UNIV

Patent Information

Application Number
CN202411859032.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

The existing graphite casing and low-density carbon casing for high-temperature calcining of lithium battery negative electrode materials have poor performance, short life, and high cost of preparation methods, which limits their wide application.

Method used

Using continuous carbon fiber reinforced silicon carbide sachet, a high-strength and wear-resistant resistant process is prepared by combining carbon fiber cloth with designated tow specifications and a silicon carbide matrix, combining simple brushing, mold clamping, sintering processes and liquid phase densification processes. Materials with properties and antioxidant properties.

Benefits of technology

It significantly improves the reliability and life of the sachet, reduces the preparation cost, and provides silicon carbide sachet products with excellent performance and low cost, suitable for sintering of negative electrode materials for lithium battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119306497A_ABST
    Figure CN119306497A_ABST
Patent Text Reader

Abstract

The invention relates to a continuous carbon fiber reinforced silicon carbide sagger and a preparation method thereof, and aims to solve the problems of poor performance and short service life of an existing graphite sagger or low-density carbon-carbon sagger for high-temperature calcination of a lithium battery negative electrode material. The saggar takes continuous carbon fiber cloth as a reinforcement body. The preparation method comprises the following steps: preparing slurry, cutting the continuous carbon fiber cloth, laying and brushing or spraying, drying and closing a mold, curing, replacing the mold, sintering, densifying again and the like. According to the method, by controlling the content of the continuous carbon fiber cloth and the silicon carbide matrix, the oxidation resistance and the mechanical property are greatly improved while low density is considered. The strength and the service life of the prepared sagger material are far higher than those of existing sagger materials such as graphite and low-density carbon, and meanwhile the sagger material is low in raw material cost, simple in technological process, good in performance, low in cost and wide in application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention generally relates to the technical field of ceramic composite materials, and in particular to a continuous carbon fiber reinforced silicon carbide sagger and a preparation method thereof. Background Art

[0002] At present, lithium battery negative electrode materials are an important part of lithium-ion batteries. Graphite negative electrode materials need to go through the process of coating asphalt carbonization. The carbonization process requires the use of saggers as containers for raw materials during high-temperature roasting. Saggers play a key auxiliary role in the preparation of lithium-ion battery negative electrode materials. Qualified saggers must meet the mechanical strength required for calcination and have good thermal stability.

[0003] At present, the commonly used sagger is graphite sagger, which is mainly produced by mechanical processing of high-quality graphite blanks. The production of graphite blanks requires the processes of graphite raw material pre-crushing, calcination, crushing, screening, batching, kneading, pressing, roasting, impregnation, graphitization, etc. This method has a long production cycle and low efficiency. Since the internal space of the sagger is formed by mechanical chip cutting, a lot of material waste is caused, and the manufacturing cost is high. In addition, graphite is prone to cracks under repeated high-temperature thermal shock, which can easily lead to component damage and cause safety accidents. Therefore, the service life of the sagger is short.

[0004] In order to increase the service life of the sagger, but at the same time meet the low-cost process, there are currently low-cost carbon / carbon composite materials on the market as saggers for high-temperature calcination of lithium battery negative electrode materials. Compared with graphite sagger materials, carbon-carbon materials use short-cut or long-fiber needle-punched felt as reinforcement, and the mechanical properties and service life of the sagger are greatly improved. However, the strength of the low-cost carbon-carbon material used for the sagger is limited compared with graphite, and there are also problems such as low strength, poor oxidation resistance and short service life. In order to increase the service life of the sagger, it is generally still necessary to prepare an antioxidant coating on the surface of the sagger, which will increase the cost of the carbon / carbon sagger.

[0005] Therefore, if silicon carbide is used as the matrix material to prepare the sagger, the anti-oxidation problem of the sagger material can be effectively improved. Silicon carbide sagger has excellent high-temperature properties, such as high-temperature strength, high wear resistance, high corrosion resistance and low thermal expansion coefficient. Its high-temperature strength can reach more than 2000℃, its wear resistance is more than 10 times that of traditional refractory materials, and its corrosion resistance is better than other ceramic materials. In addition, silicon carbide sagger also has good thermal shock resistance and chemical stability, and can be used in various extreme environments. It is widely used in ceramics, glass, battery electrode materials and other industries.

[0006] Existing silicon carbide saggers are mostly prepared by powder sintering process, and sintered silicon carbide has the disadvantages of poor toughness, poor thermal shock resistance and high preparation cost, which limits its wide application.

[0007] Therefore, it is of great significance to develop a continuous carbon fiber reinforced silicon carbide sagger with high reliability and a preparation method thereof. Summary of the invention

[0008] The invention provides a continuous carbon fiber reinforced silicon carbide sagger and a preparation method thereof, aiming to solve the problems of poor performance and short life of graphite saggers or low-density carbon-carbon saggers used for high-temperature calcination of negative electrode materials of lithium batteries in the prior art.

[0009] The technical solution of the present invention is a continuous carbon fiber reinforced silicon carbide sagger, comprising a continuous carbon fiber cloth reinforcement and a silicon carbide matrix; the continuous carbon fiber cloth reinforcement has a surface density of 200g / m 2 -400g / m 2 The carbon fiber plain, twill or satin cloth, the fiber specification of the continuous carbon fiber cloth reinforcement is one of 3K, 6K or 12K; the volume ratio of the continuous carbon fiber cloth reinforcement in the sagger is: 30%-45vol%; the volume ratio of the silicon carbide matrix in the sagger is 25%-45%; the porosity of the continuous carbon fiber reinforced silicon carbide sagger is 15%-25%.

[0010] The present invention also provides a method for preparing the above-mentioned continuous carbon fiber reinforced silicon carbide sagger, comprising the following steps: S1. Prepare slurry; S2, cutting continuous carbon fiber cloth; S3, laying and brushing or spraying: continuous carbon fiber cloth laying and slurry coating are performed on the inner mold surface of the sagger structure; S4, drying and mold closing: After the sample processed in step S3 is dried together with the inner mold, a stainless steel pressing plate is used as an outer mold, and the inner mold and the outer mold are closed in the order of the bottom surface first and then the side surface, and the inner mold and the outer mold are fastened with stainless steel screws; S5, curing: curing the sample after tightening and mold closing; S6. Mold replacement: remove the stainless steel platen outer mold from the cured sample, use the graphite platen as the outer mold again, and fasten the inner mold and outer mold with graphite screws; S7, sintering: putting the sample after being fastened with graphite screws into a high temperature furnace for high temperature sintering, and removing the inner mold and the outer mold after sintering; S8, re-densification of the sagger, using a liquid impregnation-cracking process to densify the sample treated in step S7 to obtain the continuous carbon fiber reinforced silicon carbide sagger.

[0011] Furthermore, in the above step S1, the raw materials of the slurry include silicon carbide powder, carbon powder and silicon powder, phenolic resin and solvent ethanol; the volume ratio of silicon carbide powder, carbon powder, silicon powder, phenolic resin and ethanol is (15-30):(2-5):(5-15):(15-20):100, wherein the particle size of silicon carbide powder is 3 microns to 5 microns, the particle size of carbon powder is 1 micron to 2 microns, and the particle size of silicon powder is 1 micron to 3 microns; in the step S3, the inner mold of the sagger is a cube with five surfaces, and the five surfaces are the working surfaces for paving and painting or spraying.

[0012] Further in the above step S2: the method for cutting the continuous carbon fiber cloth is to cut the carbon fiber cloth into two shapes of cloth, A and B, wherein the shape of cloth A is a cross, the sizes of the four branches of the cross match the side sizes of the sagger, and the size of the center of the cross matches the bottom surface of the inner mold of the sagger structure; the shape of cloth B is T-shaped, the size of the horizontal part of the T-shaped matches the outer peripheral size of the sagger, and the raised part of the T-shaped is located at the center of the horizontal part and its shape matches the bottom surface of the sagger.

[0013] Furthermore, the specific method of the above step S3 is: laying the cut fiber cloth layer by layer in the order of A\B\A\B\... on the inner mold surface of the sagger structure, and after laying each layer of continuous carbon fiber cloth, brushing or spraying the slurry prepared in step S1 onto the fiber cloth until the number of layers required by the design is met; during the brushing or spraying process, the weight ratio of the slurry and the carbon fiber cloth is controlled to be (1-2): 1; in order to increase the uniform support of the fiber cloth to the sagger and form a better overall combination, the following laying scheme is designed: when the B cloth is laid in alternate layers, the connecting seams are placed on the four sides of the sagger in turn to achieve the structural integrity of the sagger.

[0014] The inner mold of the sagger structure is a cube with five surfaces serving as working surfaces, and the material of the inner mold of the sagger structure is graphite.

[0015] Furthermore, the drying in the above step S4 is room temperature drying for 4 hours to 6 hours; the curing temperature in the above step S5 is 150°C to 200°C for 2 hours to 4 hours; the sintering temperature in the above step S7 is 1400°C to 1500°C.

[0016] Furthermore, in the liquid impregnation-cracking densification process in the above step S8, the impregnation slurry is a low-cost silicon carbide precursor solution, the silicon carbide precursor is an organic silicon resin, the cracking temperature range is: 1400°C-1500°C; the number of impregnation-cracking times is 1-2 times.

[0017] The present invention also provides an application of the above-mentioned continuous carbon fiber reinforced silicon carbide sagger, which is used for sintering negative electrode materials of lithium batteries.

[0018] The advantages of the present invention compared with the prior art are: 1) The continuous carbon fiber reinforced silicon carbide sagger of the present invention uses carbon fiber cloth woven from fibers of specified tow specifications as a reinforcement, and evenly layers it in a silicon carbide matrix. Both the fiber cloth specifications and the layout of the carbon fiber cloth make the sagger material have a very high load-bearing capacity, greatly improving the reliability of the sagger. At the same time, compared with the disordered chopped fiber reinforcement, the fracture toughness of the sagger material is significantly increased by the layered fiber cloth, and severe brittle fracture will not occur during use due to temperature changes or uneven force, and the reliability of use is significantly improved; 2) The continuous carbon fiber reinforced silicon carbide sagger of the present invention controls the volume of the continuous carbon fiber cloth, the silicon carbide matrix and the porosity of the matrix, so that the oxidation resistance and mechanical properties of the sagger are greatly improved while taking into account the oxidation resistance and low density of the sagger; 3) In the preparation method of the present invention, the silicon carbide matrix includes directly added silicon carbide powder and part of the silicon carbide matrix components obtained by sintering silicon powder and carbon powder. On the one hand, compared with the conventional chemical vapor deposition (CVI) or precursor conversion (PIP) process, the cost of preparing the sagger is greatly reduced; on the other hand, the sagger forms a stronger bonding interface with the continuous carbon fiber cloth during the formation of the silicon carbide matrix through the sintering reaction of silicon powder and carbon powder, so that the mechanical properties of the sagger are improved; 4) In the preparation method provided by the present invention, the silicon carbide sagger material is obtained by simple brushing, mold closing, sintering process and 0-2 cycles of liquid phase process densification. The strength and service life of the prepared sagger material are much higher than those of existing graphite, low-density carbon-carbon and other sagger materials. At the same time, the cost of raw materials is low and the process is simple. The prepared silicon carbide sagger has good performance and low cost, and has broad application prospects. The preparation method of the present invention can successfully prepare silicon carbide sagger products with excellent performance and low cost, and has the advantages of simple operation, low cost, high efficiency, etc., providing a new approach for low-cost and long-life applications. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] These and / or other aspects and advantages of the present invention will become more clear and easier to understand from the following detailed description of the embodiments of the present invention in conjunction with the accompanying drawings, in which: Figure 1 This is a schematic diagram of the product appearance structure of the continuous carbon fiber reinforced silicon carbide sagger obtained in an embodiment of the present invention; Figure 2 This is an overall schematic diagram of a continuous carbon fiber reinforced silicon carbide sagger inner mold according to an embodiment of the present invention; Figure 3 This is an overall schematic diagram of the inner mold and outer mold of the continuous carbon fiber reinforced silicon carbide sagger after the mold is closed in an embodiment of the present invention; Figure 4The load-displacement curve of the bending test process of the continuous carbon fiber reinforced silicon carbide sagger material in Example 2 of the present invention; Figure 5 Schematic diagram of the shapes of type A cloth and type B cloth in an embodiment of the present invention; (a) is type A cloth, and (b) is type B cloth. DETAILED DESCRIPTION

[0020] In order to enable those skilled in the art to better understand the present invention, the present invention is further described in detail below in conjunction with the accompanying drawings and specific implementation methods.

[0021] Example 1 A method for preparing continuous carbon fiber reinforced silicon carbide sagger Mix and stir evenly the silicon carbide powder with an average particle size of 5 microns, the carbon powder with an average particle size of 1 micron, the silicon powder with an average particle size of 1 micron, the phenolic resin and the solvent ethanol in a volume ratio of 15:5:15:15:100. Lay the cut 3K plain weave fiber cloth with a surface density of 200g on the designed sagger inner mold (the fiber cloth is cut into two shapes A and B, respectively as shown in Figure 5 As shown in (a) and (b), it can be seen that the A-type cloth is centered on the bottom of the sagger, and the cross center of the A-type cloth is laid on the bottom of the sagger, and the four branches correspond to the four sides of the sagger respectively; the B-type cloth is the horizontal long side used to lay the four sides of the sagger, and the bulge in the top center is used to lay the bottom of the sagger). After laying each layer of fiber cloth, the prepared slurry is brushed and sprayed on the fiber cloth until the number of layers required by the design is met. The weight ratio of slurry to carbon fiber is 1:1; the above samples are dried at room temperature for 4 hours. Then a stainless steel pressing plate is used as the outer mold, and the inner mold and the outer mold are molded in the order of the bottom first and then the side, and the inner and outer molds are fastened to the designed size with stainless steel screws. The sample after fastening and molding is placed in a 180 oven for curing for 4 hours. After curing, the stainless steel pressing plate and the stainless steel screw mold are removed from the sample, and the graphite pressing plate is used as the outer mold again, and the inner and outer molds are fastened with graphite screws; the sample fastened with graphite screws is placed in a 1400℃ high-temperature furnace for 2 hours of high-temperature sintering to obtain the continuous carbon fiber reinforced silicon carbide sagger. The density of the obtained silicon carbide sagger is 1.77g / cm 3 , open porosity is 18.5% and flexural strength is 61.83MPa.

[0022] Example 2 A method for preparing continuous carbon fiber reinforced silicon carbide sagger Mix and stir evenly the average 3-micron silicon carbide powder, the average 2-micron carbon powder, the average 3-micron silicon powder, the phenolic resin and the solvent ethanol in a volume ratio of 30:2:5:20:100. Lay the cut 6K twill fiber cloth with a surface density of 320g on the designed sagger core mold. After laying each layer of fiber cloth, brush and spray the prepared slurry on the fiber cloth until the number of layers required by the design is met. The overall schematic diagram of the obtained sagger inner mold is shown as follows: Figure 2 As shown, the weight ratio of slurry to carbon fiber is 2:1; the above sample is dried at room temperature for 6 hours. Then a stainless steel pressing plate is used as the outer mold, and the inner mold and the outer mold are molded in the order of the bottom surface first and then the side surface, and the inner and outer molds are fastened to the designed size with stainless steel screws. The overall schematic diagram after the inner mold and the outer mold are molded is shown in Figure 3 As shown, the sample after tightening and mold closing is placed in a 200°C oven for curing for 2 hours. The stainless steel pressing plate and stainless steel screws are removed from the cured sample, and the graphite pressing plate is used as the outer mold again, and the inner and outer molds are fastened with graphite screws; the sample fastened with graphite screws is placed in a 1500°C high-temperature furnace for 1 hour for high-temperature sintering. Finally, the obtained sagger is vacuum impregnated with a silicone resin solution with a solid content of 50%, taken out and dried, and then placed in a high-temperature pyrolysis furnace at 1400°C for pyrolysis to obtain the continuous carbon fiber reinforced silicon carbide sagger. The density of the obtained silicon carbide sagger is 1.87g / cm 3 The open porosity is 8.45%, the bending strength is 82.92MPa, and the appearance structure of the obtained sagger is as follows Figure 1 shown. Figure 4 Shown is the load-displacement curve of the continuous carbon fiber reinforced silicon carbide sagger material during the bending test.

[0023] Example 3 A method for preparing continuous carbon fiber reinforced silicon carbide sagger The average 3-micron particle size of silicon carbide powder, the average 2-micron particle size of carbon powder, the average 3-micron particle size of silicon powder, phenolic resin and solvent ethanol are mixed and stirred evenly in a volume ratio of 25:3:10:18:100. The cut 12K satin fiber cloth with a surface density of 400g is laid on the designed sagger core mold. After each layer of fiber cloth is laid, the prepared slurry is brushed and sprayed on the fiber cloth until the number of layers required by the design is met. The weight ratio of slurry to carbon fiber is 1.5:1; the above samples are dried at room temperature for 5 hours. Then a stainless steel pressing plate is used as the outer mold, and the inner mold and the outer mold are molded in the order of the bottom surface first and then the side surface, and the inner and outer molds are fastened to the designed size with stainless steel screws. The sample after fastening and molding is placed in a 200 oven for curing for 3 hours. Remove the stainless steel pressing plate and stainless steel screws from the cured sample, use the graphite pressing plate as the outer mold again and use graphite screws to fasten the inner and outer molds; place the sample fastened with graphite screws in a 1400℃ high-temperature furnace and keep it warm for 1 hour for high-temperature sintering. The obtained sagger is vacuum impregnated with a silicone resin solution with a solid content of 50%, taken out and dried, and then placed in a high-temperature pyrolysis furnace at 1500℃ to obtain the continuous carbon fiber reinforced silicon carbide sagger. Repeat the impregnation and pyrolysis of 50% silicone resin solution to obtain the continuous carbon fiber reinforced silicon carbide sagger. The density of the obtained silicon carbide sagger is 1.89g / cm 3 , open porosity is 7.47% and flexural strength is 90.77MPa.

[0024] Comparative Example 1 The silicon carbide powder with an average particle size of 5 microns, phenolic resin and solvent ethanol are mixed and stirred evenly in a volume ratio of 30:15:100. The cut 3K fiber cloth is laid on the designed sagger core mold. After each layer of fiber cloth is laid, the prepared slurry is brushed and sprayed on the fiber cloth until the number of layers required by the design is met. The weight ratio of slurry to carbon fiber is 1:1; the above sample is dried at room temperature for 4 hours. Then a stainless steel pressing plate is used as the outer mold, and the inner mold and the outer mold are molded in the order of the bottom surface first and the side surface later, and the inner and outer molds are fastened to the designed size with stainless steel screws, and the sample after fastening is placed in a 180 oven for curing for 4 hours. The stainless steel pressing plate and stainless steel screws are removed from the cured sample, and a graphite pressing plate is used as the outer mold again, and the inner and outer molds are fastened with graphite screws; the sample fastened with graphite screws is placed in a 1400℃ high-temperature furnace for 2 hours of high-temperature sintering to obtain the continuous carbon fiber reinforced silicon carbide sagger. The density of the obtained silicon carbide sagger is 1.76g / cm 3 , open porosity is 18.6% and flexural strength is 38.55MPa.

[0025] In combination with commonly used graphite and C / C material saggers for sintering lithium ion electronic negative electrode materials, a comparative table of the sagger performances of the embodiments of the present invention and comparative example 1 is shown in Table 1 below.

[0026] Table 1 Comparison of performance of saggers used for sintering of lithium ion electronic negative electrode materials in the examples and common

[0027] Note: C / C used in saggers is generally low-cost and low-density C / C; graphite is low-cost, high-purity or fine-grained graphite.

[0028] It can be seen that Example 1 of the present invention adopts a plain woven fiber cloth with a 3K surface density of 200g to prepare a C / SiC composite material sagger. The bending strength of the sagger after molding and sintering once reaches 61.83MPa. Adding silicon powder and carbon powder to the slurry can effectively improve the bonding performance between the matrix and the fiber cloth layer after reaction.

[0029] Compared with Example 1, in addition to using fiber cloths with different surface densities and slurry components with different ratios, Examples 2 and 3 also perform liquid phase densification on the materials after the first sintering, respectively. The densification process can increase the matrix content and density of the silicon carbide matrix of the C / SiC composite material sagger. From the implementation results, the strength of the C / SiC composite material sagger obtained in Example 2 and Example 3 is significantly improved, and the bending strength reaches 82.92MPa and 90.77MPa, respectively.

[0030] Compared with Example 1, the raw materials, proportions and sintering temperatures used in Comparative Example 1 are similar, but the difference is that silicon powder is not added to the slurry. The lack of silicon powder leads to weak bonding between the continuous carbon fiber cloth reinforcement and the silicon carbide matrix and the continuous carbon fiber cloth reinforcement layers in the direct C / SiC composite material sagger. Therefore, the strength of the prepared C / SiC composite material sagger is also low, with a bending strength of only 38.55 MPa. The low strength cannot meet the use of the sagger material.

[0031] The embodiments of the present invention have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and variations will be apparent to those of ordinary skill in the art without departing from the scope and spirit of the described embodiments. Therefore, the scope of protection of the present invention should be subject to the scope of protection of the claims.

Claims

1. A continuous carbon fiber reinforced silicon carbide sagger, characterized in that: It includes a continuous carbon fiber cloth reinforcement and a silicon carbide matrix; The continuous carbon fiber cloth reinforcement has a surface density of 200g / m 2 -400g / m 2 Carbon fiber plain or twill or satin cloth, the fiber specification of the continuous carbon fiber cloth reinforcement is one of 3K, 6K or 12K; The volume ratio of the continuous carbon fiber cloth reinforcement in the sagger is 30%-45vol%; the volume ratio of the silicon carbide matrix in the sagger is 25%-45%; the porosity of the continuous carbon fiber reinforced silicon carbide sagger is 15%-25%.

2. A method for preparing a continuous carbon fiber reinforced silicon carbide sagger according to claim 1, characterized in that: The following steps are involved: S1. Prepare slurry; S2, cutting continuous carbon fiber cloth; S3, laying and brushing or spraying: continuous carbon fiber cloth laying and slurry coating are performed on the inner mold surface of the sagger; S4, drying and mold closing: After drying the sample obtained in step S3 together with the inner mold, a stainless steel pressing plate is used as an outer mold, and the sample together with the inner mold and the outer mold are molded in the order of the bottom surface first and then the side surface, and the inner mold and the outer mold are fastened with stainless steel screws; S5, curing: curing the sample after tightening and mold closing; S6. Mold replacement: remove the stainless steel platen outer mold from the cured sample, use the graphite platen as the outer mold again, and fasten the inner mold and outer mold with graphite screws; S7, sintering: placing the sample after being fastened with graphite screws in a high temperature furnace for high temperature sintering, removing the inner mold and the outer mold after sintering, and obtaining the continuous carbon fiber reinforced silicon carbide sagger.

3. The method for preparing a continuous carbon fiber reinforced silicon carbide sagger according to claim 2, characterized in that: It also includes step S8: Step S8, re-densification of the sagger, densification of the sample after the treatment in step S7 by liquid impregnation-cracking process to obtain the continuous carbon fiber reinforced silicon carbide sagger.

4. The method for preparing a continuous carbon fiber reinforced silicon carbide sagger according to claim 3, characterized in that: In step S1, the raw materials of the slurry include silicon carbide powder, carbon powder and silicon powder, phenolic resin and solvent ethanol; the volume ratio of silicon carbide powder, carbon powder, silicon powder, phenolic resin and ethanol is (15-30): (2-5): (5-15): (15-20): 100, wherein the particle size of silicon carbide powder is 3 microns to 5 microns, the particle size of carbon powder is 1 micron to 2 microns, and the particle size of silicon powder is 1 micron to 3 microns; In step S3, the inner mold of the sagger is a cube with five surfaces.

5. The method for preparing a continuous carbon fiber reinforced silicon carbide sagger according to claim 4, characterized in that: The specific method of step S2 is: cutting the carbon fiber cloth into two shapes of cloth, A and B, wherein the shape of cloth A is a cross, the sizes of the four branches of the cross match the size of the side of the sagger, and the size of the center of the cross matches the surface of the bottom surface of the inner mold of the sagger structure; the shape of cloth B is T-shaped, the size of the horizontal part of the T-shaped matches the size of the outer periphery of the sagger, and the raised part of the T-shaped is located at the center of the horizontal part and its shape matches the bottom surface of the sagger.

6. The method for preparing a continuous carbon fiber reinforced silicon carbide sagger according to claim 5, characterized in that: The specific method of step S3 is: laying the cut fiber cloth layer by layer in the order of A\B\A\B\... on the inner mold surface of the sagger structure, and after laying each layer of continuous carbon fiber cloth, brushing or spraying the slurry prepared in step S1 on the fiber cloth until the number of layers required by the design is met; during the brushing or spraying process, the weight ratio of the slurry to the carbon fiber cloth is controlled to be (1-2):1; When B cloth is laid in intervals, the connecting seams are placed on the four sides of the sagger in sequence to achieve the structural integrity of the sagger; The inner mold material of the sagger structure is graphite.

7. The method for preparing a continuous carbon fiber reinforced silicon carbide sagger according to claim 2, characterized in that: The drying in step S4 is performed at room temperature for 4 to 6 hours; The curing temperature in step S5 is 150° C.-200° C., and the curing time is 2 hours to 4 hours.

8. The method for preparing a continuous carbon fiber reinforced silicon carbide sagger according to claim 2, characterized in that: The sintering temperature in step S7 is 1400°C-1500°C.

9. The method for preparing a continuous carbon fiber reinforced silicon carbide sagger according to claim 3, characterized in that: In the liquid impregnation-cracking densification process in step S8, the impregnation slurry is a low-cost silicon carbide precursor solution, the silicon carbide precursor is an organic silicon resin, the cracking temperature range is: 1400°C-1500°C; the number of impregnation-cracking times is 1-2 times.

10. The use of the continuous carbon fiber reinforced silicon carbide sagger according to claim 1, characterized in that: It is used for sintering negative electrode materials of lithium batteries.

Citation Information

Patent Citations

  • Silicon carbide coated graphite box pot and manufacturing process thereof

    CN109534837A

  • High-temperature-resistant composite material as well as preparation method and application thereof

    CN115872751A

  • Preparation method of carbon-carbon sagger preform, carbon-carbon sagger and preparation method of carbon-carbon sagger

    CN116947520A

  • Sagger forming process

    CN117819997A

  • Carbon / carbon-silicon carbide gradient composite material sagger and preparation method and application thereof

    CN119143514A

Cited By

  • Splicing type mould pressing graphite sagger and preparation method thereof

    CN120736901A

  • Preparation method of high-density sagger and sagger thereof

    CN122212791A